2021
DOI: 10.52082/jssm.2021.759
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Lower Extremity Kinematics during the Overhead Deep Squat by Functional Movement Screen Score

Abstract: It is unclear if the Functional Movement Screen (FMS) scoring criteria identify kinematics that have been associated with lower extremity injury risk. The purpose was to compare lower extremity kinematics of the overhead deep squat (OHDS) during the FMS between individuals who were grouped on FMS scoring. Forty-five adults who were free of injury and without knowledge of the FMS or its scoring criteria (males = 19, females = 26; height = 1.68 0.08 m; mass = 70.7 7 13.0 kg). Three-dimensional lower extremity ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
(74 reference statements)
5
4
0
Order By: Relevance
“…Normal mean (± standard deviation) kinematic and kinetic data figures were created in the most current Visual 3D (Vx64) software and graphed as the percent squat from 0 to 100%. This is consistent with time-normalized reporting of the OHDS used by Heredia et al where graphic presentation is reported in a percentage from 0 to 100% [15].…”
Section: Data Reduction and Analysissupporting
confidence: 90%
See 4 more Smart Citations
“…Normal mean (± standard deviation) kinematic and kinetic data figures were created in the most current Visual 3D (Vx64) software and graphed as the percent squat from 0 to 100%. This is consistent with time-normalized reporting of the OHDS used by Heredia et al where graphic presentation is reported in a percentage from 0 to 100% [15].…”
Section: Data Reduction and Analysissupporting
confidence: 90%
“…Sagittal and transverse plane motion during the squat followed a highly predictable pattern and demonstrated the least variability. The mean peak knee flexion of approximately 123 degrees was comparable to that reported by others [10,15]. However, our data did not distinguish subjects by FMS TM score, whereas Butler and Heredia found that participants with FMS TM scores of 1 and 2 demonstrated less peak flexion than those with an FMS TM score of 3 [10,15].…”
Section: Knee Joint Kinematicssupporting
confidence: 75%
See 3 more Smart Citations